(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2023)
Image retrieval used in CBIR is based on image features viz. color, texture, shape, size etc. CBIR system is used in various areas like medical, academic, art, fashion, entertainment. Image classification framework projects a linear training complexity and great interpretability which is missing in customary models. Feature coding which is a key component of image classification, greatly influences in terms of both accuracy and speed. For this, the most imminent BoF framework is used. There are numbers of feature coding techniques available. Out of these techniques, Super Vector Coding (SVC) outperforms in both speed and accuracy, as it reconstructs a feature without deviation.